Mdm2 targeting via PROteolysis TArgeting Chimeras (PROTAC) is efficient in p53 wildtype, p53-mutated, and abemaciclib-resistant estrogen receptor-positive cell lines and superior to mdm2 inhibition - Alina Goerg; Gerhard Piendl; Veruschka Albert; Olaf Ortmann; Anja Kathrin Wege; Gero Brockhoff (BMC Cancer)
Abstract Purpose The human double minute 2 homolog hdm2, alias mdm2, is the main negative-regulator of the tumor suppressor p53. In that capacity, mdm2 is a promising but not yet utilized molecular target for the treatment of breast cancer, however, its inhibition by small molecules is rather inappropriate. Instead, mdm2 degradation by PROteolysis TArgeting Chimeras (PROTAC) is expected to be highly specific, to exhibit pronounced efficiency and minimal side effects. Moreover, there is profound evidence that mdm2-specific PROTAC degraders are efficient even in tumor cells harboring p53 loss-of-function mutations. Methods We comparatively treated p53 wildtype / abemaciclib-sensitive and -resistant MCF-7, as well as p53-mutated T-47D estrogen receptor-positive breast cancer cells in-vitro with the mdm2 inhibitor AMG-232 and an mdm2 PROTAC degrader. The molecular signaling as a function of mdm2 inhibition and degradation was assessed and cell viability and cell cycle kinetics were monitored. In addition, potential PROTAC effects on the expression of immune-related markers MHC-I, MHC-II, PD-L1, PD-L2, and CD276 were determined. Results PROTAC treatment considerably attenuated cell proliferations and was superior to mdm2 inhibition in p53 wildtype and even in p53-mutated cells. Proliferation-associated pathways were significantly but differentially affected, including p73, retinoblastoma protein, and the transcription factor E2F1. MHC-I and CD276 were significantly downregulated. Conclusion The data reveal deeper insight into PROTAC-induced molecular mechanisms in luminal breast cancer cells with and without p53 mutations. The study provides the basis to evaluate the therapeutic applicability of anti-mdm2 PROTAC degraders in an appropriate preclinical in-vivo setting, for example in humanized tumor mice.